STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) MELALUI PENGEMBANGAN POTENSI PARIWISATA KABUPATEN MANGGARAI BARAT - Rosmiati Rosmiati; Trisakti Handayani; Rohmad Widodo (University of Muhammadiyah Malang, 2018)
ABSTRAKPemerintah Kabupaten Manggarai Barat mempunyai peran penting dalam memajukan daerahnya, salah satunya dengan mengembangkan potensi yang ada. Dengan mengoptimalkan potensi yang ada di Manggarai Barat, khususnya dari sektor pariwisata agar bisa meningkatkan Pendapatan Daerah. Penelitian ini bertujuan untuk : (1) Mendeskripsikan upaya pengembangan potensi pariwisata dalam meningkatkan Pendapatan Asli Daerah, (2) Menganalisis kendala yang dihadapi Pemerintah Daerah dalam pengembangan potensi pariwisata, (3) Menjelaskan solusi yang dilakukan Pemerintah Daerah dan mengatasi kendala. Penelitian ini menggunakan teknik penelitian deskriptif kualitatif. Pengumpulan data diperoleh dengan teknik observasi, wawancara dan dokumentasi. Adapun informan yang digali informasinya adalah sekretaris dinas kebudayaandan pariwisata, kepala bidang pengembangan, kepala bidang promosi, pemandu wisata dan pengunjung wisata di Kabupaten Manggarai Barat. Berdasarkan penelitian diperoleh hasil sebagai berikut:(1) Strategi Pemerintah Daerah untuk meningkatkan Pendapatan Asli Daerah melalui pengembangan potensi pariwisata telah dilakukan dan dimasukan dalam Renstra, namun belum begitu maksimal, (2) Kendalanya yaitu: faktor masyarakat, kurangnya kualitas SDM, anggaran dana terbatas, belum optimalnya sarana dan prasarana, kurangnya kerjasama, ketatnya persaingan pasar dan masih belum tersedianya sarana promosi. (3) Solusinya yaitu mengadakan pokdarwis, meningkatkan kualitas SDM, mengoptimalkan pengeluaran maupun pemasukan dana, peningkatan sarana dan prasarana, meningkatkan koordinasi antar dinas, peningkatan kualitas produk, mengoptimalkan sarana promosi.Kata Kunci : Strategi, Pemerintah Daerah, Potensi Pariwisata.ABSTRACTFurthermore, the local government of West Manggarai holds the crucial role indeveloping the region by means of optimizing the existing potentialities. In accordance with the societal perception regarding the condition of eastern regions of Indonesia that are categorized as underdeveloped regions, it is of requirement for local government to alternate such paradigm. It might be by optimizing the potentialities that entail West Manggarai, particularly on tourism sector, in addition to increase the revenue. Therefore this research was intended to: (1) describe the efforts of developing the tourism potentiality in developing the locally-generated revenue in West Manggarai; (2) analyze the barriers faced by the local government in developing the tourism potentiality; (3) formulate the possible solutions for local government to overcome the barriers. Moreover, this research accommodated descriptively qualitative research design in whichthis research was to systematically and conscientiously provide a vision of actual facts and characteristics of particular population. In addition, it aimed to solve the actual issues and collect the data. Furthermore, the data were originally collected from observation, interview, and documentation. In fact, the informants recruited included the secretary of Department of Tourism and Culture, the head of field development tour-guide (1 person), and tourist (1 person) of West Manggarai. Alluding to the research that had been piloted,there were some results as being explicated as follows: (1) the strategies of localgovernment in developing the revenue by means of developing the tourism potentiality had been implemented and inserted into the strategic plan, but they had not been maximally successful yet; (2) the barriers faced in developing the tourism potentiality comprised societal factor, lack of quality regarding human resource, limited budgets, ineffectiveness of supporting facilities, lack of collaboration with private parties, the sharp competition ofmarket, and the unobtainability of tourism promotion facilities, such as websites; and (3) the possible solutions to overcome the barriers were by: establishing aware group of tourism, upgrading the quality of human resource, optimizing the expenditures and revenues, developing the supporting facilities, strengthening the coordination of each department, upgrading the quality of products, and optimizing the promotion facilities.Keywords: The Strategies, Local Government, Tourism Potentiality.